Effects of ketogenic diet on the classification and functional composition of intestinal flora in children with mitochondrial epilepsy - Wang, Jing; Huang, LIjuan; Li, Hua; Chen, Guohong; Yang, Liming; Wang, Dong; Han, Hong; Zheng, Guo; Wang, Xu; Liang, Jianmin; He, Weijie; Fang, Fang; et al. (Frontiers in Neurology, 2023)
The ketogenic diet (KD) has shown excellent performance in the treatment of refractory epilepsy, but how it works is not yet fully understood. Gut microbiota is associated with various neurological disorders through the brain-gut axis. Different dietary patterns have different effects on the composition and function of gut microbiota. Here, by analyzing fecal samples from some patients with mitochondrial epilepsy before and after KD treatment through 16SrRNA sequencing, we found that KD intervention reduced the abundance of Firmicutes in the patient's gut, while the abundance of Bacteroidota increased in the KD group. LefSe analysis showed that Actinobacteriota, Phascolarctobacterium had significant advantages in the control group, while Bacteroides increased significantly after KD intervention, especially Bacteroides fragilis. Functional analysis showed that there were significant differences in 12 pathways in level 3. These changes suggest that KD can change the composition and diversity of the gut microbiota in patients and affect their function.Changes in specific bacterial groups in the gut may serve as biomarkers for the therapeutic effects of KD on epilepsy.